On the Significance of Religion for Human Rights. - Kollontai, Pauline. (Religion Matters Series, 2023)
Addressed to policy makers, academics and practitioners worldwide, this progressive and engaging volume offers provides pragmatic studies which further the interreligious, international and interdisciplinary understanding of the role of religion in the area of human rights.